Women in the Budget How is the Allocation of Government Expenditure Based on the Pro Gender Budget (PGB) in Batang Regency? Pro Gender Government Expenditure Budget in Batang Regency - Hidayati, Arina; Setiawan, Hendy (Bestuurskunde: Journal of Governmental Studies, 2023)
Batang Regency has high level of domestic violence, with the majority of victims being women. This situation is contrary to the local government’s responsive budget plans that include gender equality points. The reality, the women’s welfare in Batang Regency is still lower than those of men. This study aimed to analyze the effect of local government’s responsive budget allocations to women's welfare in Batang Regency. This study used a qualitative method with a case study approach. The study was conducted for five months (May-September) and used the type of Spradley domain analysis. Results of this study showed that the regional government of Batang Regency had implemented a gender-responsive budget in the Regional Medium Term Development Plan (RPJMD). However, this regional expenditure did not affect the gender development index. The regional expenditure realization program set by the regional government of Batang Regency was also still incomplete. This is due to the operations of the KITB, which provides employment opportunities for all genders, but has not been included in the regional government work programs through the allocated budget.